2023
DOI: 10.1101/2023.01.16.22283804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The central nervous system’s proteogenomic and spatial imprint upon systemic viral infections with SARS-CoV-2

Abstract: In COVID-19 neurological alterations are noticed during the systemic viral infection. Various pathophysiological mechanisms on the central nervous system (CNS) have been suggested in the past two years, including the viral neurotropism hypothesis. Nevertheless, neurological complications can also occur independent of neurotropism and at different stages of the disease and may be persistent. Previous autopsy studies of the CNS from patients with severe COVID-19 show infiltration of macrophages and T lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 148 publications
1
3
0
Order By: Relevance
“…1 a). Notably, this is in line with a recent study that demonstrated a strong inflammatory response in brain stems of deceased COVID-19 patients [ 24 ]. Next, we investigated whether the vagus nerve is directly affected by COVID-19.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1 a). Notably, this is in line with a recent study that demonstrated a strong inflammatory response in brain stems of deceased COVID-19 patients [ 24 ]. Next, we investigated whether the vagus nerve is directly affected by COVID-19.…”
Section: Resultssupporting
confidence: 92%
“…This is supported by our findings of strong endothelial inflammatory responses in vagus nerves of COVID-19 patients similar to the transcriptional profiles of the neurovascular units in the CNS [ 15 , 29 ]. Thereby, the vagus nerve might serve as additional gateway for SARS-CoV-2 infiltration of the brain stem and CNS [ 24 ]. Across different cell types, SARS-CoV-2 induced a strong interferon response independent of the viral load.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Interestingly, focal upregulation of EC MCAM was recently observed in the context of neuroCOVID. 10 …”
mentioning
confidence: 99%